2019
DOI: 10.3390/f10110982
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized Surface Layer on Poplar Wood Fabricated by Fire Retardant and Thermal Densification. Part 2: Dynamic Wettability and Bonding Strength

Abstract: In continuation of our former study on a novel combined treatment of nitrogen–phosphorus fire retardant and thermomechanical densification on wood, this study focuses on the dynamic wettability and the bonding strength. The contact angle was measured using the sessile drop method and the surface energy was calculated according to the van Oss method. Water surface penetrating and spreading is analyzed by both the Shi and Gardner model and the droplet volume changing model. The results reveal that the combined t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 18 publications
(21 reference statements)
0
4
0
1
Order By: Relevance
“…In our previous studies, it has been reported that the heat treatment process declined the surface abrasion and Shore D hardness, as well as bonding capacity (Chu et al, 2020), and that an enhanced surface layer could be generated by an impregnated chemical agent and thermal compression (Chu et al, 2019). However, there are few studies on the degree of thermal degradation of the heat-treated wood at 0-3 mm surface layer to the best of the authors knowledge, although there are several studies involving the overall properties of the wood (Schneid et al, 2014;Costa et al, 2020).…”
Section: Introduction 1 Uvodmentioning
confidence: 95%
See 1 more Smart Citation
“…In our previous studies, it has been reported that the heat treatment process declined the surface abrasion and Shore D hardness, as well as bonding capacity (Chu et al, 2020), and that an enhanced surface layer could be generated by an impregnated chemical agent and thermal compression (Chu et al, 2019). However, there are few studies on the degree of thermal degradation of the heat-treated wood at 0-3 mm surface layer to the best of the authors knowledge, although there are several studies involving the overall properties of the wood (Schneid et al, 2014;Costa et al, 2020).…”
Section: Introduction 1 Uvodmentioning
confidence: 95%
“…Sve u svemu, intenzitet toplinske modifikacije topolovine u površinskom sloju varira, a vrijednosti H R i ΔE* 1 mogu se iskoristiti za karakterizaciju i predviđanje intenziteta modifikacije i stupnja toplinske razgradnje površinskog sloja toplinski modificirane topolovine. KLJUČNE RIJEČI: toplinska obrada; intenzitet modifikacije; tvrdoća; boja; topolovina or water (Rahimi et al, 2019). High-temperature heat treatment of wood usually reduces its mechanical properties (Wu et al, 2019;Widmann et al, 2012), and increases overall brittleness (Hughes et al, 2015;Yildiz et al, 2006).…”
Section: Introduction 1 Uvodunclassified
“…Investigations of wettability and surface roughness have been performedinvolving different densification processes (Bekhta and Krystofiak 2016, Bekhta et al 2018, Chu et al 2019, Zao et al 2020, Gao and Huang 2022, Gullo et al 2023, with different results.Temperature, time and pressure act in the process, along with the compaction rate, which should be especially considered since it dictates the behavior as a function of the chemical and anatomical structure of wood of different species. Densification is considered an effective to wayimprove the mechanical properties of wood (Luan et al 2022, Cabral et al 2022, butto achieve good results, information is required about the optimal combinations of treatment parameters to improve the properties of specific woods (Schwarzkopf 2020, Cabral et al 2022.…”
Section: Introductionmentioning
confidence: 99%
“…There are different ways to harden and make wooden material more stable against pathogens, pests, and fire [9,10]. Most of the methods involved in making wood additionally fire-resistant do not use green methods, but rather toxic chemicals [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…There are different ways to harden and make wooden material more stable against pathogens, pests, and fire [9,10]. Most of the methods involved in making wood additionally fire-resistant do not use green methods, but rather toxic chemicals [9,10]. Some modern methods even use materials such as silicon carbide or graphene oxide, which have excellent efficiency, but high price [11].…”
Section: Introductionmentioning
confidence: 99%